Blood and urine early treatment response biomarkers in HIV-associated disseminated tuberculosis - Linda Boloko; Marcia Vermeulen; Bianca Sossen; Abulele Bekiswa; Phiona E. Namale; Chad Centner; Robert J. Wilkinson; Charlotte Schutz; Graeme Meintjes; David A. Barr (Southern African Journal of HIV Medicine)
Background: Treatment response biomarkers are needed in the care of patients hospitalised with HIV-associated tuberculosis (TB).